Resistance to immune checkpoint inhibitors in the treatment of metastatic renal cancer - A. A. Izmailov; R. R. Rakhimov; A. V. Sultanbayev; K. V. Menshikov; I. R. Gilyazova; V. M. Zabelin; A. A. Izmailov (Сибирский онкологический журнал, 2023)
Over the past 5 years, checkpoint inhibitors including anti-CTLA-4 and anti-PD-1/PD-L1 blockers have changed approaches to therapy of metastatic renal cell cancer. However, more than 55 % of patients with advanced kidney cancer remain resistant to immunotherapy. This paper refects the causes that lead to primary and acquired resistance to immune checkpoint inhibitors during the treatment of metastatic renal cell cancer. The purpose of the study was to elucidate the mechanisms underlying resistance to checkpoint inhibitors during the treatment of metastatic kidney cancer. Material and Methods. A literature search was conducted using Pubmed database in the time interval between 2010 and 2023. We identifed 286 publications of which 59 were relevant for our review. Results. There are many factors that contribute to primary or acquired resistance to immunotherapy, including factors associated with the tumor cell as well as tumor microenvironment factors. Conclusion. Many innovative approaches to overcoming resistance to monoclonal antibodies are being investigated in clinical trials. In connection with the advent of new methods, the cellular composition of the tumor microenvironment and its role in the emergence of tumor resistance to immunotherapy are becoming increasingly clear. New biomarkers are emerging to help identify the best candidates for immunotherapy in metastatic kidney cancer. However, they require further study.